Sistem Aplikasi Kalkulator Indeks Massa Tubuh (IMT) dengan Menggunakan Bahasa C++ - Muchtar Ali Setyo Yudono; Eko Susilo Budi Utomo; Idrus Firdaus; Dede Ajudin; Ajat; Yasser Arafat; Febriansyah; Hamid; Odi Akhyarsi (Fidelity : Jurnal Teknik Elektro, 2022)
The Body Mass Index (BMI) calculator system is a program that can help users monitor their weight. The purpose of this research paper is to create a body mass index calculator that will make it easier for users to calculate body mass index values, classify body weight based on body mass index, and manage it. The C++ programming language is used in this procedure. The script software is visually designed and built into the Delphi IDE toolbox. The IMT calculator system was successfully designed using the C++ programming language, and the system worked well. The calculator can calculate, categorize, and provide suggestions to make it easier to determine the value of body mass index, group weight based on ideal body mass index, and manage disease so that it can be prevented early.